2011
DOI: 10.1273/cbij.11.52
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Antimicrobial Agents Targeting the Bacterial RNA Polymerase by High-Throughput Virtual Screening

Abstract: Bacterial RNA polymerase (RNAP) is the least popular target for antibiotics, and currently Rifampicin is only an approved drug for clinical use. However, RNAP is essential for bacterial growth and survival, and it can be a promising target for antimicrobial agents. Thus, we decided to search new antimicrobial agents for RNAP by virtual screening. When virtual screenings are performed, certain compounds repeatedly appears on hits covering a wide range of targets (frequently hitters). Also, the performance of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 35 In preliminary assay screening of UT-01320 ( 3 ) against the potential drug targets for non-replicating Mtb, it was observed that 3 inhibited E. coli, S. aureus, and M. smegmatis RNA polymerases with the IC 50 values of the 100-150 nM range (vs IC 50 120 nM for rifampicin against E. coli RNA polymerase) ( Figure 5B ), whereas, 3 did not inhibit electron transport systems, menaquinone biosynthesis, Mtb serine/threonine kinases (PKnA and B), and DNA gyrase. 36 , 37 , 38 , 39 Capuramycin ( 1 ) and SQ 641 ( 2 ) did not inhibit bacterial RNA polymerases even at 100 μM concentrations. Figure 5 summaries MurX and RNA polymerase inhibitory activities of Capuramycin ( 1 ), SQ 641 ( 2 ), and UT-01320 ( 3 ).…”
Section: Resultsmentioning
confidence: 98%
“… 35 In preliminary assay screening of UT-01320 ( 3 ) against the potential drug targets for non-replicating Mtb, it was observed that 3 inhibited E. coli, S. aureus, and M. smegmatis RNA polymerases with the IC 50 values of the 100-150 nM range (vs IC 50 120 nM for rifampicin against E. coli RNA polymerase) ( Figure 5B ), whereas, 3 did not inhibit electron transport systems, menaquinone biosynthesis, Mtb serine/threonine kinases (PKnA and B), and DNA gyrase. 36 , 37 , 38 , 39 Capuramycin ( 1 ) and SQ 641 ( 2 ) did not inhibit bacterial RNA polymerases even at 100 μM concentrations. Figure 5 summaries MurX and RNA polymerase inhibitory activities of Capuramycin ( 1 ), SQ 641 ( 2 ), and UT-01320 ( 3 ).…”
Section: Resultsmentioning
confidence: 98%